Decarbonization as a Business Risk: Theoretical Insights and Empirical Evidence from the Automotive Sector - Pompella, Maurizio; Scordis, Nicos (Ekonomika, 2026)
Objective: The aim of this paper is to explore the financial and strategic implications of decarbonization from a business risk perspective. Starting from risk theory, insurance economics, and transition finance, we conceptualize decarbonization not as a linear optimization process, but as a wicked problem. We argue that firms face both tame and wild risks, and that transition risk occupies a hybrid position that challenges conventional insurance as well as capital market arrangements.Methods: To empirically assess whether these theoretical dynamics are explicit in corporate behavior, we focus on the automotive industry, which is most exposed to decarbonization pressures. By using ESG data (14 profile scores) and GHG emissions (Scope 1, 2, 3 – absolute and intensity-adjusted), we analyse eight global multinational companies from the automotive sector, from 2017 to 2023. We build a novel ESG-GHG Decoupling Index (DI), capturing the divergence between sustainability disclosure and emission performance.Results: Our findings highlight significant misalignments in some firms, suggesting reputational risk, strategic inconsistency, or greenwashing. We complement this with a Mahalanobis distance-based clustering, revealing instead patterns of convergence and divergence in emissions strategy.Conclusions: We conclude that ESG improvements alone are not sufficient indicators of true environmental transition, and argue for a multidimensional, risk-based framework to assess corporate decarbonization efforts.
Keywords: Decarbonization; Cost of Risk; Tame and Wild Risks; Mahalanobis Clustering; ESG-GHG Decoupling Index